Pengaruh Kinerja Keuangan terhadap Harga Saham Perusahaan Jasa Pertambangan dan Pertambangan di Bursa Efek Indonesia (BEI) - Rahmalia, Bella Gita; Siswoyo, Slamet Tedy (Jurnal Manajemen DIVERSIFIKASI, 2021)
This study aims to see the effect of financial performance on stock prices. The financial ratios used in this study are Return on Equity, Earning Per Share, Net Profit Margin. The research design used in this research is quantitative. The object of this research is mining and mining service companies listed on the Indonesia Stock Exchange in 2018-2020. The population in this study were 49 companies officially listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling. In order to obtain a sample of 21 companies that meet the required sample needs. Based on the research results, it shows that the variable Return on Equity (ROE) has no significant effect on stock prices, Earning Per Share (EPS) has a significant effect on stock prices, Net Profit Margin (NPM) has no significant effect on stock prices. Meanwhile, Return on Equity (ROE), Earning Per Share (EPS) and Net Profit Margin (NPM) together (simultaneously) have a significant effect on stock prices.